Pengaruh Kepemilikan Publik dan Profitabilitas Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Ida Fitriyani; Dwi Indah Lestari (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine the effect of public ownership and profitability on the timeliness of financial report submission. Secondary data used in this research is the company's audited annual financial statements. The population in this study is mining sector companies listed on the Indonesia Stock Exchange 2014-2018. The sampling technique used in this research is purposive sampling, thereby obtained 180 samples from 36 companies. The analysis technique used in this research is logistic regression analysis. The results showed that the partial public ownership does not affect the timeliness of financial report submission, while profitability positive and significant impact on the timeliness of financial report submission. Public ownership and profitability simultaneously have a positive and significant effect on the timeliness of financial report submission. Keywords: Public Ownership, Profitability and Timeliness of Financial Report Submission.